ChemInform Abstract: Ionothermal Synthesis and Structure of a New Layered Zirconium Phosphate. Issue 42 (October 2015) - Smeets, Stef; Liu, Lei; Dong, Jinxiang; McCusker, Lynne B.
Abstract The new title compound (Hpy)1.77(HEtpy)1.62 [Zr6P6O28F2 (H2O)4] (Etpy: N‐ethylpyridinium) is prepared by hydrothermal treatment of a mixture of EtpyBr as both the solvent and the template, ZrOCl2H3PO4, and HF (autoclave, 180 °C, 4 d).